Teachers and the new ICT challenges - Pramela Krish,; Noraza Ahmad Zabidi, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
Information Communication Technology (ICT) breakthroughs have brought new opportunities to restructure the learning and knowledge transfer environment. ICT technology has opened new avenues and brought new challenges to learners and teachers. The responsibility of learning has shifted to the learners and this allows the roles of teachers to change in tandem. However, we should not lose sight of the fact that teachers determine the quality of the learning that takes place, and not technology. This article discusses the changes that teachers would experience in this new learning environment and the implications on their pedagogic practice. It also shares what teachers say about using ICT in teaching